Augmented Reality-Based Interactive Learning Media: Enhancing Understanding of Chemical Bonding Concepts - Riah, Hunus (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to produce interactive learning media based on augmented reality technology on chemical bonding material and to determine students' responses to the media. Methodology: This research is a development research with Warsita development model, which includes design stage, production stage, and evaluation stage. The data obtained were analyzed descriptively. Main Findings: The results of the limited trial received positive responses from students with the percentage details obtained being 85.75% for the usability aspect, 81.80% for the illustration usage aspect, 74.57% for the future impact aspect, 79.64% for the material usefulness aspect, and 77.20% for the grammar aspect. Novelty/Originality of this study: Can be used as an alternative interactive learning media in learning activities, especially in chemical bonding materials. Can be used as input and reference in developing interactive learning media on other materials.